2022
DOI: 10.3389/fonc.2022.826040
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Perceptions of Clinical Utility of a Digital Health Tool for Electronic Patient-Reported Outcome Monitoring in Real-Life Hematology Practice. Evidence From the GIMEMA-ALLIANCE Platform

Abstract: Digital health tools are increasingly being used in cancer care and may include electronic patient-reported outcome (ePRO) monitoring systems. We examined physicians’ perceptions of usability and clinical utility of a digital health tool (GIMEMA-ALLIANCE platform) for ePRO monitoring in the real-life practice of patients with hematologic malignancies. This tool allows for the collection and assessment of ePROs with real-time graphical presentation of results to medical staff. Based on a predefined algorithm, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
7
0
3
Order By: Relevance
“…Remarkably, the systematic monitoring of PROs via web-based platforms, was also found to be associated with improved overall survival in patients with advanced cancers ( 67 , 68 ). Finally, a study examining physicians' perceptions of usability and clinical utility of a digital health tool (GIMEMA-ALLIANCE platform) for ePRO monitoring in the real-life practice of patients with hematologic malignancies found that all hematologists participating in the study agreed or strongly agreed that the platform was easy to use, and 87%, agreed or strongly agreed that ePROs data were useful to enhance communication with their patients ( 69 ). These preliminary results support the clinical utility, from the perspectives of the treating hematologist, of integrating ePROs into routine cancer care of patients with hematologic malignancies, and could be implemented in the EPC interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the systematic monitoring of PROs via web-based platforms, was also found to be associated with improved overall survival in patients with advanced cancers ( 67 , 68 ). Finally, a study examining physicians' perceptions of usability and clinical utility of a digital health tool (GIMEMA-ALLIANCE platform) for ePRO monitoring in the real-life practice of patients with hematologic malignancies found that all hematologists participating in the study agreed or strongly agreed that the platform was easy to use, and 87%, agreed or strongly agreed that ePROs data were useful to enhance communication with their patients ( 69 ). These preliminary results support the clinical utility, from the perspectives of the treating hematologist, of integrating ePROs into routine cancer care of patients with hematologic malignancies, and could be implemented in the EPC interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ePROs led to a significant difference of 13% in incidence of serious immune-related adverse events (irAEs), 7.4% lower rates of treatment discontinuation and better quality of life in patients on cancer immunotherapy. 25 Clinicians reported that ePRO data facilitated their understanding of patients’ general health status and symptoms, 12 identification of low-grade and high-grade symptomatic adverse events, 12 accurate documentation of patients’ symptoms 9 , 12 , 24 and improved patient adherence to treatment. 10 , 16 , 29 …”
Section: Benefits Of Implementing Epro Systems For Outpatient Carementioning
confidence: 99%
“…Various studies described clinician responses to ePRO data, which suggest timely/earlier intervention when symptoms of clinical concern are present. 30 , 31 These included: telephoning patients upon receiving ePRO alerts of clinically important symptoms 12 ; referrals to other healthcare professionals 19 ; mental health services 24 ; further assessments; requests for blood tests; recommendations to wait and monitor symptoms; and patient education. 19 Clinicians also stated that ePRO data were useful in the clinical management of patients and shared decision-making.…”
Section: Benefits Of Implementing Epro Systems For Outpatient Carementioning
confidence: 99%
See 2 more Smart Citations